2022
DOI: 10.1021/acsomega.2c00176
|View full text |Cite
|
Sign up to set email alerts
|

σ-Hole and LP-Hole Interactions of Pnicogen···Pnicogen Homodimers under the External Electric Field Effect: A Quantum Mechanical Study

Abstract: σ-Hole and lone-pair (lp)-hole interactions within σ-hole···σ-hole, σ-hole···lp-hole, and lp-hole···lp-hole configurations were comparatively investigated on the pnicogen···pnicogen homodimers (PCl 3 ) 2 , for the first time, under field-free conditions and the influence of the external electric field (EEF). The electrostatic potential calculations emphasized the impressive versatility of the examined PCl 3 monomers to participate in σ-hole a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…Results of M06-2X/6-311++G(d,p) in terms of distances and energies were also similar to the previously reported result in M05-2X/6-311++G(d,p) level. 8 Another study demonstrated the presence of an lp-hole in PCl 3 and the interactions between their dimers, 29 reporting “σ-hole···lp-hole” and “lp-hole···lp-hole” complexes. But again, the P⋯P distance was significantly higher than the sum of van der Waals radii, making it very unlikely that the lp-hole is involved in the formation of an electrostatically/charge-transfer driven hole interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Results of M06-2X/6-311++G(d,p) in terms of distances and energies were also similar to the previously reported result in M05-2X/6-311++G(d,p) level. 8 Another study demonstrated the presence of an lp-hole in PCl 3 and the interactions between their dimers, 29 reporting “σ-hole···lp-hole” and “lp-hole···lp-hole” complexes. But again, the P⋯P distance was significantly higher than the sum of van der Waals radii, making it very unlikely that the lp-hole is involved in the formation of an electrostatically/charge-transfer driven hole interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The pace of this work continues to accelerate even today. 33–39 Over the years, the investigations of these interactions have moved beyond halogen atoms, hence the development of analogous chalcogen or pnicogen bonds which engender robust study. 36,40–44…”
Section: Introductionmentioning
confidence: 99%